1971
DOI: 10.1042/bj1220013
|View full text |Cite
|
Sign up to set email alerts
|

Ketone-body utilization by adult and suckling rat brain in vivo

Abstract: 1. Ketone-body utilization in fed and starved adult and suckling rats has been investigated by measuring arterio-venous differences across the brain. Venous blood was collected from the confluence of sinuses and arterial blood from the femoral artery in adult rats and by cardiac puncture in suckling rats. 2. During starvation the arterio-venous difference of ketone bodies increased in proportion to their concentrations in the blood and reached a value of 0.16mm at 48h. At a given concentration of the respectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

28
293
7
5

Year Published

1974
1974
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 606 publications
(333 citation statements)
references
References 13 publications
28
293
7
5
Order By: Relevance
“…In all animals, there was a significant output of lactate and pyruvate from brain to blood. Similar results were obtained by Dahlquist and Persson (1976), except that in these animals, which were 20 days old, the influence of starvation on ketonaemia was greater than had been observed by Hawkins et al (1971). CBF was measured: the rate in anaesthetized infant rats was 48 ml 100 g-l min-1 and in adult rats it was 62 ml 100 g-l min-I, although the difference between the two age groups was not statistically significant.…”
Section: Ratssupporting
confidence: 85%
See 3 more Smart Citations
“…In all animals, there was a significant output of lactate and pyruvate from brain to blood. Similar results were obtained by Dahlquist and Persson (1976), except that in these animals, which were 20 days old, the influence of starvation on ketonaemia was greater than had been observed by Hawkins et al (1971). CBF was measured: the rate in anaesthetized infant rats was 48 ml 100 g-l min-1 and in adult rats it was 62 ml 100 g-l min-I, although the difference between the two age groups was not statistically significant.…”
Section: Ratssupporting
confidence: 85%
“…CBF was measured: the rate in anaesthetized infant rats was 48 ml 100 g-l min-1 and in adult rats it was 62 ml 100 g-l min-I, although the difference between the two age groups was not statistically significant. In infant rats, the measured oxygen uptake was considerably less than would be required for complete oxidation of the substrates extracted, whereas this was not so in adult rats, When the arteriovenous difference values for 20-day-old rats starved for 48 h obtained by Dahlquist and Persson (1976) are compared with values ob tained by Hawkins et al (1971) for 22 day-old rats starved for 16 h, the notable difference between the two studies is the total amount of substrate taken up by the brain. Extraction values for glucose and 3-hydroxybutyrate found by Hawkins et al were about 50% lower.…”
Section: Ratsmentioning
confidence: 88%
See 2 more Smart Citations
“…In contrast to awake rats, studies of barbiturate anesthetized and hyperketonemic (48-hour fast) adult rats consistently found higher ketone body contributions to total brain substrate oxidation, with values of 18% and 29% of total oxidation for [BHB] plasma of 0.64 mM and 2 mM, respectively. 28,29 In a study that compared 24-hour and 48-hour fasted rats under PB anesthesia, including an acute infusion of DL-BHB in 24-hour fasted rats ([BHB] plasma ¼ 0.83, 2.05, and 5.52 mM, respectively), Ruderman et al 30 found that ketone bodies accounted for 28%, 33%, and 68% respectively of total acetyl-CoA oxidation. For the halothaneanesthetized rats in the present study ([BHB] plasma ¼ 6.6 mM), 48% of acetyl-CoA oxidation was fueled by ketone bodies, which is in reasonable agreement with the above studies.…”
Section: Discussionmentioning
confidence: 99%